Compare Trait-state Anxiety and Perfectionism Dimensions of Mothers of Children with Anxiety Disorders and Healthy Children - Mohammad Aminaee; Rasol Roshan Chesli; Mohammad Reza Shairi; Fatemeh Moharreri (روانشناسی بالینی و شخصیت, 2015)
Anxiety disorders are the most common problems among children, which can lead to functional problems. Most family studies indicate high overlap of child anxiety disorders and his/her family.